Impact of different Streptococcus pneumoniae on the secretion of interleukin and adhesin from THP‐1 monocytes. Issue 7 (23rd June 2019) - Ren, Ping; Zhang, Jin; Yu, Lianhua; Qu, Ying; Jiang, Xinyu; Zhou, Yixia; Hu, Dakang; Gao, Chunyan
Abstract: Background: To investigate the secretion of interleukin‐1β (IL‐1β), IL‐6, IL‐10, IL‐8, and soluble intercellular adhesin molecule 1 (sICAM‐1) from THP‐1 monocytes stimulated by different Streptococcus pneumoniae ( S pneumoniae ) strains. Methods: Fifty‐eight strains of S pneumoniae were collected: ATCC49619, 23 from sputum (sd‐SP), 23 from blood (bd‐SP), and 11 from cerebrospinal fluid (CSF; cd‐SP). Such strains were cultured and suspended at 0.5 McFarland. THP‐1 monocytes were cultured and resuspended at 5.0 × 10 8 /L, which were stimulated by S pneumoniae for 4, 8, and 12 hours, respectively. The suspensions were analyzed for IL‐1β, IL‐6, IL‐10, IL‐8, and sICAM‐1 using an ELISA method. The data were assayed with SPSS 19.0. Results: Contrary to IL‐10, the concentrations of IL‐1β, IL‐6, IL‐8, and sICAM‐1 all increased first and then decreased. IL‐1β and sICAM‐1 levels in the ATCC49619 group were both higher than all the clinical S pneumoniae groups (sd‐SP, bd‐SP, and cd‐SP), IL‐6 and IL‐8 versa, and IL‐10 equal. The difference among clinical S pneumoniae groups lay only in sICAM‐1. cd‐SP group showed lower sICAM‐1 concentrations than sd‐SP and bd‐SP groups at both 4 and 8 hours. However, they became equal at 12 hours. Conclusions: The secretion summit is 8 hours for IL‐1β, IL‐6, IL‐8, and sICAM‐1, bottom for IL‐10. Different clinical S pneumoniae strains show similar ability to induce THP‐1 cells secreting interleukins. However, cd‐SP induces THP‐1 cells secreting lower sICAM‐1 than sd‐SP and bd‐SP, which may in turn facilitate its invasion into CSF.